EKSISTENSI LAGU NASIONAL DI ERA GLOBALISASI SEBAGAI PEMBENTUK NASIONALISME SISWA SD NEGERI 1 KENDAL - Khairunnisa Della (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This study discusses the existence of the national anthem in the era of globalization as a form of nationalism in elementary school students at SMP Negeri 1 Kendal, Kendal Village, Ngawi, East Java. This study aims to provide information about the national anthem's existence and role in forming the nationalist spirit of elementary school students in the era of globalization. Students are expected to appreciate and understand the intrinsic and extrinsic elements of the national song so that it can add to the spirit of nationalism which can then be implemented in life. The research method used was interviews with several SMP Negeri 1 Kendal students. The results show that the existence of the national anthem still exists. SMP Negeri 1 students sing the national anthem no more than once a week. But overall, they know various national anthems and can implement the contents of the national anthem in their lives.